PENERAPAN KOMUNIKASI INTERPERSONAL PUSTAKAWAN DALAM MENINGKATKAN KENYAMANAN PEMUSTAKA - Tabitha, Marsia Sumule G, Asrul Jaya (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2017)
ABSTRACT The problem in this research is how the role of interpersonan communication librarian in Library and Filing Service of Southeast Sulawesi Province in improving user's convenience. The purpose of this study is to determine the role of interpersonal communication librarians at the Library and Filing Service of Southeast Sulawesi Province in improving the user's convenience.The location of this research was carried out at the Library and Filing Service of Southeast Sulawesi Province. The theory used is Devito's Theory of Liliweri Alo. In this study the number of informants as much as six people to represent pemustaka. The type of data used in this study is the qualitative data and data analysis techniques used in this study qualitative descriptive analysis.The results of this study indicate that the role of Interpersonal Communication in improving the user's convenience in the Library and Filing Service of Southeast Sulawesi Province can not be separated from the Humanistic model and pragmatic model which shows that the quality of effective interpersonal communication is determined by five factors: openness, empathy, Support, Positiveness, and Equality. Of the five factors have not fully run perfectly in the main case of having a positivesense.This research is expected to give benefit and contribution of Science for Librarian especially Librarian which exist in Library and Filing Service of South East Sulawesi Province. This study is also expected to provide benefits in the development of Communication Science, especially on the research role of interpersonal communication librarians in improving the user's convenience.Keywords: Library, Interpersonal Communication, Convenience